2023
DOI: 10.1111/1365-2745.14136
|View full text |Cite
|
Sign up to set email alerts
|

Drought intensity alters productivity, carbon allocation and plant nitrogen uptake in fast versus slow grassland communities

Abstract: Grasslands face more frequent and extreme droughts; yet, their responses to increasing drought intensity are poorly understood. Increasing drought intensity likely triggers abrupt shifts (thresholds) in grassland ecosystem functioning which can implicate recovery trajectories. Here, we determined how drought intensity affects plant productivity, and plant–soil carbon (C) and nitrogen (N) cycling. We exposed model grassland plant communities with contrasting resource acquisition strategies (a fast‐ vs a slow‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…These different responses of non‐native and native plants may be attributed to their different drought tolerance as well as their ability to recover following rewetting events. Previous studies have shown that non‐native plants are less tolerant to drought than native plants (Liu et al., 2017; Oram et al., 2023; Valliere et al., 2019). In contrast, non‐native plants can take more advantages of rewetting events to recover than native plants (Zhang et al., 2022), whereas some native plants cannot recover or even experience waterlogging stress caused by rewetting events (Blom & Voesenek, 1996; Reyer et al., 2013).…”
Section: Discussionmentioning
confidence: 98%
“…These different responses of non‐native and native plants may be attributed to their different drought tolerance as well as their ability to recover following rewetting events. Previous studies have shown that non‐native plants are less tolerant to drought than native plants (Liu et al., 2017; Oram et al., 2023; Valliere et al., 2019). In contrast, non‐native plants can take more advantages of rewetting events to recover than native plants (Zhang et al., 2022), whereas some native plants cannot recover or even experience waterlogging stress caused by rewetting events (Blom & Voesenek, 1996; Reyer et al., 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Schweiger et al., 2023), designed to explicitly test mechanisms often only inferred from past drought studies (e.g. Oram et al., 2023, see Gilbert & Medina, 2016 for a similar call for crop species). For example, soil fertility and nitrogen availability have been identified as potential mediators of ecosystem sensitivity to drought (Bharath et al., 2020; Cusack et al., 2023; Luo et al., 2021; Ma et al., 2023).…”
Section: How Can Drought Experiments Be Improved?mentioning
confidence: 99%
“…Drought events alter grassland nutrient cycling, disrupt interactions between species, result in species extinction, and therewith cause severe disruptions in ecosystem structure and function (Smith et al . 2024; Oram et al . 2023; Bardgett & Caruso 2020; Ingrisch et al .…”
Section: Introductionmentioning
confidence: 99%